The Effect of a Video-Based Game Exercise Program on Motor Skills, Proprioception, and Cognitive Functions in Individuals With Intellectual Disabilities - Elif Diril; Burak Menek; Ahmet Emir; Devrim Tarakci; Ela Tarakci (Occupational Therapy International)
Conclusion: The study suggests that video-based game exercises combined with occupational therapy interventions can effectively enhance cognitive functions, functional performance, proprioception, and fine motor skills in adults with ID.